Data collection smart and simple: Evaluation and metanalysis of call data from studies applying the 5Q approach - Eitzinger, Anton (Frontiers Media, 2021)
Agricultural development projects often struggle to show impact because they lack agile and cost-effective data collection tools and approaches. Due to the lack of real-time feedback data, they are not responsive to emerging opportunities during project implementation and often miss the needs of beneficiaries. This study evaluates the application of the 5Q approach (5Q). It shows findings from analyzing more than 37,000 call log records from studies among five countries.